Mindfulness, mental health, and motives for eating tasty foods when not in metabolic need - Moore, Katherine G.; Rice, Justess D.; Gampher, John E.; Boggiano, Mary M. (Frontiers in Psychology, 2024)
Habitual consumption of highly palatable foods when not in metabolic need (HPF eating) is linked to obesity. High HPF consumption is also linked to mental health disorder (MHD) symptoms. Mindfulness-based interventions are popular treatments for obesity and MHDs, but little is known about the relationship between trait mindfulness and motive-based HPF eating. Therefore, a total of 927 young adults completed a survey that included the Palatable Eating Motives Scale-7 (which identifies Coping-, Reward enhancement-, Social-, and Conformity-eating), the Mindful Attention Awareness Scale, the Perceived Stress Scale, and demographic and body mass index (BMI) questions. An MHD questionnaire allowed a comparison of HPF eating between participants with and without various MHDs. Regressions revealed that Coping-eating was independently associated with lower mindfulness and also greater perceived stress, higher BMI, and female sex. Of these variables, only lower mindfulness was independently associated with Reward-, Social-, and Conformity-eating. Coping- and Reward-eating were more frequent in participants with versus without an anxiety disorder, depression, ADD/ADHD, and PTSD. Coping-eating was also more frequent in participants with body dysmorphic disorder. These findings warrant investigations in participants with clinically validated diagnoses for DSM-specific MHDs. Results from such investigations and the uncovered nature of associations between motive-specific HPF eating and trait mindfulness could provide novel targets to improve mindfulness-based interventions for obesity and MHDs.